Hysteretic out-of-plane behavior of the Temcor joint. (September 2015) - Xu, Shuai; Chen, Zhihua; Wang, Xiaodun; Mazzolani, Federico M.
Abstract: The Temcor system is very popular for building single layer lattice domes. The system is composed by double T aluminum extruded bars, six of them are joined together in the nodes, where are connected to a couple of circular gusset plates by means of bolted connection. This system works satisfactory under static symmetrical loading conditions in a membrane stress regime, but no sufficient information is available in case of non symmetrical loading conditions, when the out-of-plane behavior of the joints is requested. This paper is devoted to analyze the hysteretic behavior of the typical Temcor joint in full scale, under out-of-plane cyclic loading conditions, by means of both experimental and numerical approaches. The test results emphasized the main characteristics of the behavior of this joint beyond the elastic range and up to the collapse. The experimental hysteresis curves have been compared with the ones coming from an "ad hoc" numerical model, giving rise to a very satisfactory agreement. Highlights: The hysteretic out-of-plane behavior of the Temcor joint has been tested for the first time. An "ad hoc" numerical simulation model has been presented and successfully compared with the test results. The stress/strain distribution and the failure mode of the Temcor joint under out-of-plane cyclic loading conditions have been analyzed and discussed. Although Temcor joint does not represent a full-strength connection, it could still play a role in energy dissipation under extreme loading conditions.